My life with President Kennedy - Clausen, Christopher, 1942- (University of Iowa Press, 1994)
A collection of essays, written with the experiences and attitudes of one who came of age in the 1960s, which explore that "noisy spot of ground where ... public worlds intersect the private, mysterious lives of individuals and families."